Comparative Study of the outcome of the treatment with Danazol and or without Sports Brassieres in the Management of Mastalgia - barah, Hazim K.J (Journal of the Faculty of Medicine Baghdad, 2007)
Summary: Background Mastalgia is described as diffused or itching pain of the breast. Usually, active movement of heavy breast supported by weak suspensory ligaments contribute mainly to the etiology of mastalgia which is considered the most frequent complaint of women attending Al-Elwiya teaching hospital for consultation. Objective:- The aim was to minimiged breast pain in mastalgic women By wearing the sport brassieres with or without the Use of danazol Patient and method :- Tow hundred and fifty cyclic and non cyclic women suffering from some degrees of mastalgia were chosen randomly from breast clinic of AL-Elwiya teaching hospital from June 2004 till August 2005. The mastaligic women were divided into 3 groups: group A M’as prescribed to take 200 mg. danazol daily ,group B M’as instructed to wear the sport brassieresl while group C M’as prescribed to take 100 mg. danazol daily plus wearing the sport brassieres .The duration of the project M’as 12 weeks .All women under study were educated to complete a breast pain chart using visual analogue scale ,(VAS). Results: The outcome of the breast pain study revealed that ,the combined use of sport brassieres plus the intake of 100 mg.danazol associated with highly significant decrease in VAS with low side effects Conclusion: The management of mastagic suffering women M’as the combined use of the sport brassieres beside the intake of 100 mg. danazol which decreased breast pain and minimized side effects